1997
DOI: 10.1073/pnas.94.25.13630
|View full text |Cite
|
Sign up to set email alerts
|

Opposing mitogenic and anti-mitogenic actions of parathyroid hormone-related protein in vascular smooth muscle cells: A critical role for nuclear targeting

Abstract: A BSTR ACTParathyroid hormone-related protein (PTHrP) is a prohormone that is posttranslationally processed to a family of mature secretory forms, each of which has its own cognate receptor(s) on the cell surface that mediate the actions of PTHrP. In addition to being secreted via the classical secretory pathway and interacting with cell surface receptors in a paracrine͞autocrine fashion, PTHrP appears to be able to enter the nucleus directly following translation and influence cellular events in an ''intracri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
215
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(233 citation statements)
references
References 37 publications
16
215
2
Order By: Relevance
“…They clearly demonstrated that PTHrP possesses a double signalling on MCF-7: an antimitogenic pathway mediated by the membrane receptor and a second wave of signalling, pro-proliferative and antiapoptotic, based on nuclear localisation of the peptide. The same dual effect had also been described in vascular smooth muscle cells in 1997 (Massfelder et al, 1997).…”
Section: Sirsupporting
confidence: 73%
“…They clearly demonstrated that PTHrP possesses a double signalling on MCF-7: an antimitogenic pathway mediated by the membrane receptor and a second wave of signalling, pro-proliferative and antiapoptotic, based on nuclear localisation of the peptide. The same dual effect had also been described in vascular smooth muscle cells in 1997 (Massfelder et al, 1997).…”
Section: Sirsupporting
confidence: 73%
“…We have previously shown that PTHrP modulates cell proliferation via both the autocrine/paracrine and intracrine pathways in MCF-7 human breast cancer cells and PC-3 human prostate cancer cells [50,51]. Similar effects on proliferation have been reported for vascular smooth muscle cells [52]. The same may apply to LoVo cells.…”
Section: Discussionsupporting
confidence: 60%
“…37 In cells, other than breast cancer, NLS in PTHrP has been shown to be required for growth. For example in vascular smooth muscle cells, nuclear targeting of PTHrP was reported to be pivotal in mitogenesis 27 and in chondrocytes nuclear localisation promoted protection from apoptosis. 25 When the influence of PTHrP-(67-101) in MCF-7 cells incubated with taxotere was examined, it was found that PTHrP-(67-101) did not significantly increase the percentage of cells resistant to taxotere-induced apoptosis, which possibly suggests that it has a growth-promoting role rather than a survival role in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…35 for review) and has been shown to be required for growth in various cells types. 25,27,28 The role of midregion in breast cancer has only recently been investigated. 29 In our study we show that midregion PTHrP containing NLS spanning amino acid sequences of 87 to 101, is essential for midregion-induced growth in breast cancer cells such as MCF-7 and MDA-MB231.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation